KEMATANGAN KARIR MAHASISWA PSIKOLOGI ISLAM BERDASARKAN GENDER, ASAL SEKOLAH DAN KEAKTIFAN ORGANISASI - Murisal Murisal (Kafa`ah: Journal of Gender Studies, 2020)
This study is aimed to describe the maturity of students' career choices because they are important after graduating from college and looking for work. Field findings on Islamic Psychology students of UIN Imam Bonjol Padang are still many students anxious and doubtful in their choice, especially students of rare study programs who are interested, while students of study programs who are interested in such as Islamic Psychology believe that their career choice is clearer. This study is purposed to analyze the elements of gender, organizational activeness, and school origin, their relationship with career maturity. The research was conducted in the Islamic Psychology Department using quantitative methods; the population was all students, totaling 656 people, with a sample of 132 people who were selected using the quota sampling technique. Data were collected using a career maturity scale measuring instrument and then analyzed using descriptive statistics and t-test and one-way ANOVA. The results showed that there was no difference in career maturity between male and female students. This indicates that women view careers the same as men. This study also shows that there is no difference in career maturity between students who are active in organizations and those who are not. This indicates that the gender factor does not affect career maturity and activeness in campus organizations. Other results of this study indicate that there is no difference in career maturity based on school origin. Both students who come from Islamic boarding schools, MA, SMA, and SMK tend to have the same career maturity after being at the University